Experimental investigations of CO2 adsorption behavior in shales: Implication for CO2 geological storage - Zheng, Sijian; Sang, Shuxun; Wang, Meng; Liu, Shiqi; Huang, Kai; Feng, Guangjun; Song, Yu (Frontiers in Earth Science, 2023)
Injecting CO2 into shale reservoirs has dual benefits for enhancing gas recovery and CO2 geological sequestration, which is of great significance to ensuring energy security and achieving the ‘Carbon Neutrality’ for China. The CO2 adsorption behavior in shales largely determined the geological sequestration potential but remained uncharted. In this study, the combination of isothermal adsorption measurement and basic petro-physical characterization methods were performed to investigate CO2 adsorption mechanism in shales. Results show that the CO2 sorption capacity increase gradually with injection pressure before reaching an asymptotic maximum magnitude, which can be described equally well by the Langmuir model. TOC content is the most significant control factor on CO2 sorption capacity, and the other secondary factors include vitrinite reflectance, clay content, and brittle mineral content. The pore structure parameter of BET-specific surface area is a more direct factor affecting CO2 adsorption of shale than BJH pore volume. Langmuir CO2 adsorption capacity positive correlated with the surface fractal dimension (D1), but a significant correlation is not found with pore structure fractal dimension (D2). By introducing the CSLF and DOE methods, the research results presented in this study can be extended to the future application for CO2 geological storage potential evaluation in shales.